An infrared microspectroscopic study of plasters and pigments from the Neolithic site of Bestansur, Iraq. (June 2016) - Godleman, Jessica; Almond, Matthew J.; Matthews, Wendy
Abstract: Infrared (IR) spectroscopy and microspectroscopy (μ-IR) supported by environmental scanning electron microscope–energy dispersive X-ray analysis (ESEM-EDX) has been utilised to investigate the technology and use of multi-coloured architectural plasters and pigments by Neolithic communities at the archaeological site of Bestansur, Iraq, c. 7600 BCE. Sub-samples of architectural materials and pigments were analysed using IR spectroscopy and fragile samples and thin sections were analysed using μ-IR and ESEM-EDX to determine the mineralogical and elemental composition of individual components and layers and the history of construction and use of three large rectilinear buildings. In addition, experimental investigations were undertaken into the application of IR to study the firing of calcium carbonate and of clays to investigate if this technique was able to detect evidence of fired-lime materials and of reddening of building materials by fire. Whilst the IR analysis alone was not able to characterise the plasters and pigments, when combined with ESEM-EDX the minerals responsible for pigmentation in the samples were clearly identified. The green clay was determined to be local celadonite-bearing marine clays. The red pigment was found to contain iron, most likely in the form of hematite. The black pigment contained manganese and iron, likely to be present as manganese dioxide and magnetite. The investigations of firing indicate that a hard white exterior may come from fired-lime while a reddish silty clay wall surface had probably not been subject to high-temperature burning. Analysis of a series of wall plasters and pigments from Building 8 (pre-7600 BCE) revealed experiment and development in technologies and materials throughout the occupation of the building, which in the final sequence resemble those from significantly later level at the site of Çatalhöyük, Turkey (c. 7000 BCE).